Post a New Question


posted by on .

What would you do...

(4)^(3/square root 2) ÷ 16^(2*square root 2) ?

  • Math - ,

    Recognize that
    16^(2*square root 2)= (4^2)^(2sqrt2)
    = 4^(4sqrt2)

    So your expression can be written
    = 4^[(3/sqrt2)-(4sqrt2)]
    = 4^[(3/2)sqrt2-4sqrt2]
    = 4^[-(5/2)sqrt2]
    = 2(-5sqrt2)
    I might have made a mistake somewhere, so be sure to verify the steps.

Answer This Question

First Name:
School Subject:

Related Questions

More Related Questions

Post a New Question